Association between Fasting Blood Glucose-HbA1c Ratio with Independence Status and Clinical Outcomes of Acute Ischemic Stroke Patients - Fatwa, T. Reza; Imran, Imran; Buchari, Buchari (Enrichment: Journal of Multidisciplinary Research and Development, 2025)
Background: Stroke remains the second leading cause of mortality worldwide and the primary contributor to long-term disability. The stress hyperglycemia, calculated as the fasting blood glucose (FBG)–HbA1c ratio, has been proposed as a marker reflecting acute metabolic imbalance relative to chronic glycemic status, with potential prognostic value in acute ischemic stroke. Objectives: This study aimed to evaluate the association between the FBG–HbA1c ratio and functional independence as well as clinical outcomes in acute ischemic stroke patients. Methods: An analytical observational study employing a cross-sectional design was conducted at Dr. Zainoel Abidin General Hospital. Consecutive sampling was utilized to recruit patients with acute ischemic stroke who fulfilled the inclusion criteria. The FBG–HbA1c ratio was calculated and analyzed in relation to functional independence using the Barthel Index (BI) and clinical outcome using the Modified Rankin Scale (mRS). Pearson Product Moment Correlation test was used to determine the relationship between these variables. Results: A total of 61 patients were included. The FPG–HbA1c ratio demonstrated a significant negative correlation with the Barthel Index (R = –0.43; p = 0.04) and a significant positive correlation with the mRS (R = 0.508; p = 0.03). Conclusion: The FBG–HbA1c ratio showed significant correlations with both functional independence and clinical outcomes, indicating its potential as a simple and reliable prognostic marker. A higher ratio reflects greater stress-induced hyperglycemia, which is associated with poorer neurological function and outcomes in acute ischemic stroke patients